Anti-tumor activity of capecitabine and vinorelbine in patients with anthracycline- and taxane-pretreated metastatic breast cancer: Findings from the EORTC 10001 randomized phase II trial - (:unkn) unknown (CHURCHILL LIVINGSTONE, 2008)
The aim of this randomized phase II study was to evaluate the anti-tumor activity and safety of capecitabine and vinorelbine in patients with metastatic breast cancer pretreated with taxanes and anthracyclines. We planned to randomize 72 patients to capecitabine 1250 mg/m(2) orally bid days 1-14 or vinorelbine 30 mg/m(2) i.v. days 1 and 8, both given every 3 weeks. The study was stopped due to poor accrual with 47 patients enrolled. Responses were seen in 2/23 patients treated with capecitabine (8.7%; 95% CI 1.1-29.0) and 3/24 patients treated with vinorelbine (12.5%; 95% CI 2.7-32.4). Median progression-free survival was 2.8 and 2.6 months, and median overall survival was 9.3 and 11.0 months, in the capecitabine and vinorelbine arms, respectively. There was more hematologic toxicity, neurotoxicity, and nausea/vomiting with vinorelbine and more diarrhea and hand-foot syndrome with capecitabine. The anti-tumor activity of capecitabine and vinorelbine seems to be comparable, but the toxicity profiles are different. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: breast cancer; capecitabine; vinorelbine; efficacy; toxicity; monotherapy; INTRAVENOUS VINORELBINE; 1ST-LINE CHEMOTHERAPY; FIRST-LINE; PACLITAXEL; MULTICENTER; THERAPY; WOMEN; CMF